ANALISIS HASIL TANGKAPAN KEPITING RAJUNGAN (Portunnus pelagicus) DAN UDANG PUTIH (Peneaus marguiensis) PADA ALAT TANGKAP SERO DI HABITAT BERBEDA - Tenriware . (Jurnal Harpodon Borneo, 2013)
Portunnus pelagicus and Penaeus marguiensis are export commodity which haveimportant value because have a delicious falvour and high nutritious. This studyexamined the catch of small Portunnus pelagicus and Penaeus marguiensis in different habitats, analyzed the carapace width-weight Portunnus pelagicus relationship and carapace length-weight Penaeus marguiensis and review the LMATm. The method using capture experiment method in a crib of sero for 16 trips in the estuary, mangroves, and seagrass habitats. The analysis using analysis of varians (ANOVA), Tukey MeanDifferent Test, biometric analysis, and Proportion analysis of the catch. The result found that there was nothing Portunnus pelagicus escape from experimental crib net (4 cm) and inversely proportional to the white Penaeus marguiensis. The range size of Portunnus pelagicus caughted from 6,0 to 15,2 cm and white Portunnus pelagicus from 5,0 to 16,7 cm. The growth of Portunnus pelagicus and white Penaeus marguiensis are allometrik negative. Portunnus pelagicus carapace width and weight in their respective habitats significantly different (P0,05). The proportion of allowable catch of white Penaeus marguiensis catch in each habitat is less than 50%, whereas the Portunnus pelagicus in seagrass habitat is 77,97%. Key words : Portunnus pelagicus, Penaeus marguiensis, lengt at first maturity,allometrik negatif